Sistim Inforamsi Administrasi Sekolah di Kabupaten Gorontalo - Adriyanto B. Angio; Dian Novian; Nikmasari Pakaya (Diffusion: Journal of Systems and Information Technology, 2021)
AbstrakSchool Administration at the depertment of Education and Culture of Gorontalo district, Gorontalo Province has challenges in terms of the file management – the teacher and student files are not in digital forms and require large storage container that is centered on an only single location. The difficulty in checking these files is due to the lacking of direct integration between the schools and the department of education and culture. The optimization of the management of school administration is aimed to facilitate each school to digitally manage the administration and ease the department to receive this report. This research applies the Design Science Research Method ( DSRM) in designing a school administration information system. The final result is analysis and conclusion on the basis of the application of a school administration information system. The result creates an application that is able to optimize the school data management as it integrates school, teacher, and student data along with teacher and student data management in a single location. Digital data storage is the best alternative to manage both teacher and student data in order to be easily accessed when required. Basides, the data can also be sorted based on the name category to help identify data shortages with ease.Keywords : School Administration, DSRM